Implementation of Integrated Wi-Fi Security using RADIUS, LDAP, and Captive Portal at PT XYZ - Ahya Taufiq Akbar; Ardiansyah, Rizky; Adzikirani, Adzikirani (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
In the digital era, securing enterprise Wi-Fi networks is critical to safeguard data integrity and control user access. PT XYZ confronts escalating cybersecurity risks—including unauthorized access, brute-force attacks, and credential sharing—necessitating a robust yet efficient authentication framework. This paper proposes and implements an integrated Multi-Factor Authentication (MFA) architecture combining RADIUS, Lightweight Directory Access Protocol (LDAP), and a Captive Portal to enhance Wi-Fi security. The solution enforces layered access control: RADIUS authenticates device MAC addresses, LDAP validates user identities against a centralized directory, and the Captive Portal applies Role-Based Access Control (RBAC) to enforce granular network permissions. A SOPHOS XGS 3100 firewall complements this setup by filtering traffic and blocking malicious login attempts. Performance evaluation shows the system supports up to 289 concurrent users with a peak CPU utilization of 29.09% and stable memory usage at 48%. Quality of Service (QoS) tests yield average download and upload speeds of 141 Mbps and 153 Mbps, respectively, ensuring consistent performance during peak usage. Security robustness is validated via penetration testing, including Deauthentication and Brute Force attacks; password cracking using Hashcat with full ASCII character set requires an estimated 998 years. Results confirm that the integrated MFA approach significantly mitigates unauthorized access risks while maintaining high network performance. This work offers practical guidance for enterprises aiming to strengthen Wi-Fi infrastructure against modern cyber threats.